Can Haitian Higher Education Rise from the Rubble? - Dumay, Harry (International Higher Education, 2010)
Haitian higher education received catastrophic damage from the earthquake in 2009. The rebuilding of higher education is a priority for Haiti for educating the country's elites and achieving economic growth and innovation. In rebuilding Haitian higher education after the earthquake, pre-existing issues regarding an improvement of access and the governance, and an increase of full-time professors must be addressed.